2020
DOI: 10.12659/msm.921613
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Alcohol Consumption and Drinking Motives Among Korean Medical Students

Abstract: Departmental sources Background:Physicians who have healthy lifestyles can provide quality healthcare to their patients and keep themselves healthy. There is little data on the prevalence of drinking behaviors and problems among East Asian medical students. Here, we explored alcohol use and drinking motives among medical students in Korea. Material/Methods:A questionnaire-based, multicenter, cross-sectional study was carried out in 323 students from 5 medical colleges in Korea between July and October 2016. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 46 publications
(83 reference statements)
2
24
0
4
Order By: Relevance
“…Interestingly, most male students drink to relax or socialize, while most female students consume alcohol for the beverages’ taste or flavor. Other studies have also shown that drinking motives can differ between male and female students [ 24 ]. Among women, associations between drinking motives and the hourly AC rate were observed, and also, interactions between drinking motives and the impact of the number of friends on the hourly consumption rate [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, most male students drink to relax or socialize, while most female students consume alcohol for the beverages’ taste or flavor. Other studies have also shown that drinking motives can differ between male and female students [ 24 ]. Among women, associations between drinking motives and the hourly AC rate were observed, and also, interactions between drinking motives and the impact of the number of friends on the hourly consumption rate [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…The use of alcohol is a growing public health concern all over the world; it is associated with risk factors for disability, preventable mortality, and crime [1][2][3][4][5][6][7][8]. It is a rising problem especially among young people, including students [2][3][4][5][7][8][9][10][11]. Their alcohol intake is higher than that of their peers not attending universities, as well as the general adult population [2,5].…”
Section: Introductionmentioning
confidence: 99%
“…It is a rising problem especially among young people, including students [2][3][4][5][7][8][9][10][11]. Their alcohol intake is higher than that of their peers not attending universities, as well as the general adult population [2,5]. It has been estimated that one in three people who abuse alcohol in their youth will become addicted [10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations